Clinical Manifestations and Diagnosis of Acromegaly - Gloria Lugo; Lara Pena; Fernando Cordido (International Journal of Endocrinology)
Acromegaly and gigantism are due to excess GH production, usually as a result of a pituitary adenoma. The incidence of acromegaly is 5 cases per million per year and the prevalence is 60 cases per million. Clinical manifestations in each patient depend on the levels of GH and IGF-I, age, tumor size, and the delay in diagnosis. Manifestations of acromegaly are varied and include acral and soft tissue overgrowth, joint pain, diabetes mellitus, hypertension, and heart and respiratory failure. Acromegaly is a disabling disease that is associated with increased morbidity and reduced life expectancy. The diagnosis is based primarily on clinical features and confirmed by measuring GH levels after oral glucose loading and the estimation of IGF-I. It has been suggested that the rate of mortality in patients with acromegaly is correlated with the degree of control of GH. Adequately treated, the relative mortality risk can be markedly reduced towards normal.